Assessing Antipredator Behavior and the Potential to Enhance It in a Species of Conservation Concern. (22nd February 2023) - Kopack, Christopher J.; Broder, E. Dale; Fetherman, Eric R.; Fitzpatrick, Ryan M.; Angeloni, Lisa M.
Abstract: Animal behavior has the potential to guide the management of populations at risk of extirpation. This includes insights into how animals respond to novel predators and whether those responses can be enhanced to improve survival. Training hatchery‐reared fish to recognize predators has been proposed as a way to reduce postrelease mortalities in the wild. Identifying the presence of innate predator recognition and the capacity for learning to recognize predators in specific species or populations can inform conservation management practices. Here, antipredator behavior (time spent moving and distance from a predator) and the efficacy of predator training were assessed for three populations of a species of conservation concern, the Arkansas Darter Etheostoma cragini, which is vulnerable to predation by esocid predators like the introduced Northern Pike Esox lucius . Arkansas Darters demonstrated some innate ability to recognize and respond to a novel esocid predator and also responded to predator cues (training), although the direction of the response to cues was opposite our prediction. Populations differed in their response to the predator treatment, highlighting the value of managing populations separately. Although the fitness consequences of exposure to predator cues remain to be tested in Arkansas Darters, our results suggest that antipredator behavior is innate and that exposure to predator cues does affect behavior; however, whether or how those behavioral changes affect survival is unclear. This study demonstrates the importance of testing enrichment practices and incorporating behavioral observations into conservation programs to guide population‐specific management decisions.